(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Introduction: Therapeutic drug monitoring (TDM) measures the level of medications within the biological fluids. Valproic acid (VPA) is a narrow therapeutic index anti-epileptic. Measurement of its level is essential for the evaluation of safety and efficacy. Aim was to evaluate the benefit of TDM services in patients taking Valproic acid with respect to outcome improvement and prevention of adverse events linked to dosage errors, Methodology The cohort was designed to take random samples of patients taking Valproic acid, measuring their VAP blood levels at the correct time. Patient demographic data were collected through face-to-face and phone interviews and from patient charts. Results Results indicated that most patients were male and below 18 years of age. No toxicity was observed in the patient. Very few patients experienced side effects and attacks per week. Patients had no knowledge of medical history, Renal Function Test (RFT), Liver Function Test (LFT), Protein Level, and other medications. Discussion The study found poor education of patients about therapeutic drug monitoring, and TDM is available in private facilities only. The patient had no education about Renal and liver function test protein levels and other medications being used by them. The study also found that side effects and frequency of attacks per week were not effects by valproic acid blood levels.